Prevalence and Impact of Violence Against Healthcare Workers in Brazilian Emergency Departments: A National Survey. - Dorn de Carvalho, Julia M.; McGuire, Sarayna S.; Oliveira, Lucas L. R.; Bellolio, Fernanda; Ranzani, Otávio T.; A. M. Pinheiro Besen, Bruno; Penna Guimarães, Helio; Mullan, Aidan F.; Camila Lunardi, Maria; Hajjar, Ludhmila A.; Maia, Ian Ward A. (Western Journal of Emergency Medicine: Integrating Emergency Care with Population Health, 2025)
Introduction: Workplace violence (WPV) is a significant occupational hazard in healthcare, with emergency departments (EDs) recognized as high-risk environments. Although globally significant, data from Latin America remain scarce. In this study we aimed to evaluate the prevalence and effects of WPV on healthcare workers in Brazilian EDs. Methods: We conducted a cross-sectional survey of healthcare workers in Brazilian EDs. Respondents indicated verbal and physical violence experienced within the preceding six months, along with associated psychological and occupational impacts. Univariable models identified significant associated factors, followed by multivariable models to determine independent associated factors of WPV. We reported results as adjusted odds ratios (aOR) with 95% confidence intervals. Statistical analyses were performed in R v4.4.1, and significance was defined as P < .05. Results: The response rate was 19.1% (1,255/6,570), Of those responses, 61.3% (769/1,255) met the inclusion criteria and were included in the analysis. Of all respondents, 84.0% were physicians. Respondents indicated 79.6% (612/769) occurrence of WPV, including verbal abuse (79.5%) and physical assault (12.1%). Physical assaults against co-workers were witnessed by 40.3% of respondents. Perpetrators included visitors (85.3%), patients (80.7%), and co-workers (35.8%). The absence of institutional preventive measures was associated with increased WPV (aOR, 2.47; 95% CI, 1.71-3.57; P < .001), while the presence of security staff reduced WPV (aOR, 0.61; 95% CI, 0.42-0.89; P = .01). Indicated impact included post-traumatic stress symptoms (88.4%), considering leaving their job (49.5%), impaired workplace performance (75.2%), and time off work (10%), including 11.5% permanently leaving. Conclusion: Workplace violence is highly prevalent in Brazilian EDs, with substantial psychological and occupational consequences. The absence of protocols or preventive measures may increase WPV risk, emphasizing the urgent need for public policies to protect healthcare workers in emergency settings.